1993
DOI: 10.1105/tpc.5.5.501
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of DNA sequence requirements for Dissociation state I activity in tobacco.

Abstract: Our objective was to test whether the double Ds structure correlated with Dissociation state I activity @e., high frequency of chromosome breakage and low frequency of reversion) in maize exhibited similar properties in tobacco. A genetic assay was established to test double Ds and related structures for their ability to cause loss of the linked marker genes streptomycin phosphotransferase and P-glucuronidase in transgenic tobacco. An engineered double Ds element and a simple Ds element showed behavior consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 31 publications
2
52
0
Order By: Relevance
“…The abberant intrachromatid transposition or SIN model (Doring et al, 1984(Doring et al, , 1989English et al, 1993) proposes that two directly oriented Ds ends on the same chromatid undergo aberrant transposition. In contrast, the abberant interchromatid transposition or SIS model suggests that, after replication, a 5'end on one and a 3'end on the other daughter chromatid combine to form an aberrant transposition complex (Greenblatt, 1984;Fedoroff et al, 1989;English et al, 1993English et al, , 1995Weil and Wessler, 1993). English et al (1995) have consistently shown that the SIS mechanism predominates in tobacco.…”
Section: A Model For the Strand Selectivity Of Ac Transpositionmentioning
confidence: 99%
“…The abberant intrachromatid transposition or SIN model (Doring et al, 1984(Doring et al, , 1989English et al, 1993) proposes that two directly oriented Ds ends on the same chromatid undergo aberrant transposition. In contrast, the abberant interchromatid transposition or SIS model suggests that, after replication, a 5'end on one and a 3'end on the other daughter chromatid combine to form an aberrant transposition complex (Greenblatt, 1984;Fedoroff et al, 1989;English et al, 1993English et al, , 1995Weil and Wessler, 1993). English et al (1995) have consistently shown that the SIS mechanism predominates in tobacco.…”
Section: A Model For the Strand Selectivity Of Ac Transpositionmentioning
confidence: 99%
“…In our previous work (English et al, 1993), we extended this idea by proposing that an excision product might be formed by ligation of the sequences that had originally flanked the excised Ds ends. The sister Chromatids would be fused at this position, forming an acentric or dicentric chromatid, and chromosome breakage would result.…”
Section: Aberrant Transpositions Usually Involve Os Ends On Sister Chmentioning
confidence: 99%
“…Thus, the empty site sequences isolated by PCR experiments (English et al, 1993) probably represent the precise positions of sister chromatid fusion or "chromatid fusion products." Other models explaining the structures that were observed would be complicated enough to make them unlikely.…”
Section: Aberrant Transpositions Usually Involve Os Ends On Sister Chmentioning
confidence: 99%
See 2 more Smart Citations